(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
As elements of aesthetic values, pests and as food, insects are important. Mori Bombyx L. He is an insect that is economically important. In the tropics, it is an edible insect that is eaten. The Silkworm Larvae, B. Mori. They are popular for the production of silk. When the larvae are ready to pupate, silk is produced. The larval stage as well as the pupal stage of B. in this study the nutritional behaviors of Bombix mori were studied. The pupal stage had a higher protein content (21.59 percent) than 20.79 percent in the larval stage. The larva’s fat content was 17.57 percent, while the pupa’s fat content was 19.90 percent. In the larva (6.34 percent), the ash content was higher than that in the pupal stage (5.50 percent). The proteins have two iso-electric points in the larval and pupal stages. The larval just as the pupal phases of silkworm B. Mori is wealthy in proteins and different supplements that are essential to people and their domesticated animals. These phases of advancement (hatchlings and pupae) are additionally rich wellsprings of a large portion of the fundamental mineral salts vital for typical human turn of events. These phases of advancement are acceptable possibility for food handling enterprises where more noteworthy ability to ingest oil and water is required.